Effects Level of Urea in Urea Molasses Block on Daily Weight Gain of Goat Fed with Native Grass - Soebarinoto .; Rulif Setianum (Buletin Ilmu Makanan Ternak, 1988)
In general, tropical grasses have low crude protein, Ca and P. For feeding the growing ruminant supplementation is needed. Urea molasses block (UMB) was used in this experiment. Sixteen male goats of about six months of age and an initial weight 13.17 + 1.64 kg were assigned in Fully Randomized Design with four replications. Each goat was kept in an individual cage. The feeding regimes were : RO = native grass only, R1=native grass + UMB (3% w/w urea), R2=native grass + UMB (6% urea), R3=native grass + UMB (9% urea). Feeding and drinking were given ad libitum. Data measurement included : dry matter, organic matter, crude protein comsumption and weight gain. The results of this experiment showed that the UMB supplementation increased dry matter, organic matter, crude protein consumption per metabolic body weight (P<0,05). Daily gain of RO, R1, R2 and R3 were 20.54, 39.88, 36.16 and 39.28 g/day/head respectively, however there were not significantly different among R1, R2 and R3 (P>0.05). Ration with UMB supplementation (3% urea) gave the most promising result.